Modeling morphodynamic evolution in alluvial estuaries : Dissertation : submitted in fulfillment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the Degree of DOCTOR to be defended in public on Wednesday, 26 May 2010 at 10.00 hours in Delft, the Netherlands /: Dissertation : submitted in fulfillment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the Degree of DOCTOR to be defended in public on Wednesday, 26 May 2010 at 10.00 hours in Delft, the Netherlands. (2011) - Wegen, Mick van der
No abstract available